2012
DOI: 10.1007/s00404-012-2236-3
|View full text |Cite
|
Sign up to set email alerts
|

Expression pattern of PAX2 in hyperplastic and malignant endometrium

Abstract: PAX2 is expressed in hyperplastic and malignant endometrium as well as proliferative and atrophic endometrium. As the neoplastic lesion progresses from a premalignant state to endometrial cancer, PAX2 expression increases. These findings suggest that PAX2 may contribute to the development of endometrial cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 29 publications
2
17
2
Order By: Relevance
“…Kahraman et al showed that the mean percentages of PAX2 staining cells were 80.8, 96.7, 88.6, 92.7, and 99.2 with proliferative endometrium, atrophic endometrium, complex hyperplasia, complex atypical hyperplasia, and adenocarcinoma, respectively. Similar to our study, they did not find any correlation between PAX2 expression levels and the stage, histological grade, myometrial invasion, and lymph node status in cancer cases [20]. We investigated the correlation of expression of PTEN and PAX2.…”
Section: Discussionsupporting
confidence: 63%
“…Kahraman et al showed that the mean percentages of PAX2 staining cells were 80.8, 96.7, 88.6, 92.7, and 99.2 with proliferative endometrium, atrophic endometrium, complex hyperplasia, complex atypical hyperplasia, and adenocarcinoma, respectively. Similar to our study, they did not find any correlation between PAX2 expression levels and the stage, histological grade, myometrial invasion, and lymph node status in cancer cases [20]. We investigated the correlation of expression of PTEN and PAX2.…”
Section: Discussionsupporting
confidence: 63%
“…Regarding the assessment of risk of bias among the studies, for the "patient selection" domain, four studies were categorized as being at low risk of bias, because they included consecutive patients, whereas one was classified at unclear risk because it did not report this information, 15 and one was high risk because it only selected cases previously diagnosed as non-atypical hyperplasia. 14 Concerns about the applicability of this domain were considered high for one study, because it assessed only EH of women treated with progestin.…”
Section: Re Sultsmentioning
confidence: 99%
“…14 Concerns about the applicability of this domain were considered high for one study, because it assessed only EH of women treated with progestin. 15,19 For the "reference standard" domain, five studies were categorized at low risk of bias since they reported a blinded re-evaluation of specimens, whereas one was classified at unclear risk because this information was not clearly reported. 15,19 For the "reference standard" domain, five studies were categorized at low risk of bias since they reported a blinded re-evaluation of specimens, whereas one was classified at unclear risk because this information was not clearly reported.…”
Section: Re Sultsmentioning
confidence: 99%
“…PAX2 is a downstream gene in the steroid hormone receptor signal pathway and is overexpressed in endometrial cancer and benign endometrial hyperplasia compared with normal controls [12]. PAX2 expression was also found to increase as the pathological malignancy progressed [13]. In a xenotransplanted tumor model of human endometrial cancer in nude mice, increased PAX2 expression was observed in tumors with poor cell differentiation, and tumor volume as well as expression of PCNA and Bcl-2 were decreased following knockdown of PAX2 [14].…”
Section: Introductionmentioning
confidence: 99%